Successful and safe response to ibrutinib alone in treating relapsed Waldenström macrogobulinemia and related acquired von Willebrand syndrome: an option to consider. Issue 13 (10th November 2022) - Butelet, Alexandre; Poulain, Stéphanie; Jeanpierre, Emmanuelle; Srour, Micha; Nudel, Morgane; Chauvet, Paul; Bauters, Anne; Susen, Sophie; Dupont, Annabelle; de Charette, Marie
Abstract: Ibrutinib, a first-class Bruton tyrosine kinase inhibitor, is known to be associated with adverse bleeding events and has been recently approved for the treatment of relapse Waldenström macroglobulinemia (WM). Here, we report the exhaustive clinical and biological follow-up of 2 patients treated by ibrutinib alone in the context of relapsed WM with an acquired von Willebrand syndrome (AVWS) complication. In two cases, ibrutinib has been shown to be quickly efficient and safe for treating both AVWS and its underlying condition the WM, without bleeding complications. Interestingly, ibrutinib treatment brings a rapid and extended over time normalization of von Willebrand factor clearance. These observations show that ibrutinib is a valuable therapeutic option in relapsed WM patients associated with AVWS and highlighting the need for further cohort studies with long-term follow-up of patients to confirm the efficacy and safety of a treatment by ibrutinib for WM patients with AVWS complication.